OUTSOURCING AND CONSUMER SATISFACTION IN FOOD SERVICES. CASE STUDY OF THE SCHOOL OF DANCE AND THE SCHOOL OF MUSIC OF THE NATIONAL CONSERVATORY (Revista Lusófona de Economia e Gestão das Organizações, 2018)
More often companies are looking for customer satisfaction, so they focus their resources on production core-business and decentralize the remaining services througha subcontracting process - outsourcing.This study intends to find out the satisfaction level of public consumers with one sectorcovered by this strategic tool, the services of school canteens. That means, to verify the students satisfaction with the company of daily meal service; as well as the main reasons for the satisfaction/dissatisfaction.For this purpose, a review of the literature and an empirical study were carried out intwo schools with a common canteen.